Priority Analysis of The Integrated Pest Management (IPM) Implementation on Vegetable Cropping in Bumiaji Subdistrict, Batu City, East Java - Anes Putri Octasari; Aminudin Afandhi; Soemarno Soemarno (Graduate Program, 2019)
Pest control in vegetable cropping by using chemical pesticides intensively can have a negative impact on human health and environmental health. The IPM approach was an innovation that farmers need to adapt to reduce the use of chemical pesticides. This study was conducted to formulate the priority strategy for implementing IPM in Bumiaji Subdistrict. Determination of priority strategies to implementing IPM uses the Expert Choice in processing data. The method used in this study is Analytical Hierarchy Process (AHP) with the criteria used are: (1) IPM Knowledge and Perception, (2) Human quality improvement, (3) Agriculture Extension and (4) Technologies availability. Based on the result of AHP, the most decisive criteria in implementing IPM in vegetable cropping in Bumiaji Subdistrict, criteria of human quality improvement, in turn, the sub-criteria of training and behavior are the two sub-criteria that are highly prioritized.